Improving Mechanical Properties (Impact Strength and Wear Resistance) of Drilling Teeth Steel and Breakers Hammersr - هترة, علي; سلامة, احمد; الضاهر, نسيم (Latakia University Journal -Engineering Sciences Series, 2021)
The teeth of drill and crushing hammers are very important industrial tools in industrial applications, and it is important that the material from which these teeth and hammers are resistant to wear and shock is good, one of the most important materials is Hadfield high manganese steel, which contains a percentage of carbon that leads to the formation of carbides on the boundaries of crystalline grains, and thus the rapid breakage as it is characterized by strain hardening. Therefore, a solution must be found, whether by heat treatment, alloying, hardening, or other elements. The process of casting samples was done in sand molds and heat treatment (time and temperature variable) for a number of samples in addition to applying changes in the method of cooling before heat treatment and measuring the hardness, impact strength and wear resistance of the samples before and after heat treatment. The results showed an increase in hardness and consequently resistance to wear, as well as increased strength of impact as a result of heat treatment and change of the method of cooling after casting and before heat treatment, and thus the resulting steel became more durable for service conditions, which gives an economic feasibility to research in addition to its scientific importance